Avem doua cazuri : cand k este par si cand k este impar .
Caz 1 : k este impar
E = [tex] \frac{5}{6} [/tex] + [tex] \frac{3}{4} [/tex] - [tex] ( \frac{2}{3} )^{4k+1} [/tex] + [tex] ( \frac{2}{3})^{4k+1} [/tex] = [tex] \frac{5}{6} [/tex] + [tex] \frac{3}{4} [/tex] = [tex] \frac{38}{24} [/tex] = [tex] \frac{19}{12} [/tex]
Caz 2 : k este par
E = -[tex] \frac{5}{6} [/tex] - [tex] \frac{3}{4} [/tex] + [tex] (\frac{2}{3}) ^{4k+1} [/tex] - [tex] ( \frac{2}{3})^{4k+1} [/tex] = - [tex] \frac{5}{6} [/tex] - [tex] \frac{3}{4} [/tex] = - [tex] \frac{38}{24} [/tex] = - [tex] \frac{19}{12} [/tex]